1999
DOI: 10.1002/(sici)1097-0290(19990305)62:5<593::aid-bit11>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Backward extraction of reverse micellar encapsulated proteins using a counterionic surfactant

Abstract: The back-extraction of proteins encapsulated in AOT reverse micelles was performed by adding a counterionic surfactant, either TOMAC or DTAB. This novel backward transfer method gave higher backward extraction yields compared to the conventional method with high salt and high pH of the aqueous stripping solution. The protein activity was maintained in the resulting aqueous phase, which in this case had a near neutral pH and low salt concentration. A sharp decrease of the water content was observed in the organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…When a non-ionic surfactant Tween80 was introduced into the ionic RMs, the interaction between the anionic AOT head groups and the enzyme at the micellar interface decreased, which might suppress the hydrophobic and electrostatic interactions of enzyme molecules with the AOT molecules. 3,4 This phenomenon is similar to those reported in other recent works. 3 In addition, it is worth mentioning that the optimum W 0 was practically unchanged before and after Tween80 was added into the AOT reverse micellar system, while a change from 22 to 18 occurred in the TTAB reverse micellar system.…”
Section: Resultssupporting
confidence: 92%
“…When a non-ionic surfactant Tween80 was introduced into the ionic RMs, the interaction between the anionic AOT head groups and the enzyme at the micellar interface decreased, which might suppress the hydrophobic and electrostatic interactions of enzyme molecules with the AOT molecules. 3,4 This phenomenon is similar to those reported in other recent works. 3 In addition, it is worth mentioning that the optimum W 0 was practically unchanged before and after Tween80 was added into the AOT reverse micellar system, while a change from 22 to 18 occurred in the TTAB reverse micellar system.…”
Section: Resultssupporting
confidence: 92%
“…Jarudilokkul once reported that adding a counterionic surfactant caused the electrostatic interaction between oppositely charged surfactant molecules. This leads to a rapid collapse of the reverse micelles, and a subsequent sharp decrease of the water content in the organic phase, resulting in a rapid transfer of the proteins into the stripping aqueous phase and little damage to the biological activity of lysozyme, nuclease A and cytochrome C [11] . So the effect of addition of CTAB, a cationic surfactant, on backward extraction was investigated (Fig.…”
Section: Extraction Of Subtilisin Carlsberg By Aot/isooctane Reverse mentioning
confidence: 99%
“…Phase separation was then achieved by centrifuging at 5000 rpm for 5 min, and the remaining protein in the aqueous phase was detected by high-performance liquid chromatography (HPLC). The extracted lysozyme in the reverse micellar phase was then back-extracted into an aqueous phase in 1.5-mL test tubes by adding a cationic surfactant (60 mM TOMAC) in isooctane as described by Jarudilokkul et al (1998). The mixture was then centrifuged at 12,000 rpm for 2 min to achieve phase separation, and the aqueous phase was then analyzed using HPLC.…”
Section: Equilibrium Line Determinationmentioning
confidence: 99%